Duplication of the Urinary Tract Occurring in One Family - Husein Alatas; Soemarso Indiarto; Usman Alwi (Paediatrica Indonesiana, 1978)
Duplication of the urinary tract occurring in one family is reported. The penetration of this anomaly among them was not equal. The father had a bifid ureter on the right side. Among his children, one had right bifid pelvis and the other two bilateral double kidney. The smallest child had aÂ  non-functioning right upper kidney associated with an ureterocele causing trouble in micturition and recurrent infection. After surgical correction the symptoms disappeared.